Long Term Leases, Problems of Taxation, Finance, and Accounting (Book). - Webster, Morris N. (The Accounting Review, 1955)
Reviews the book "Long Term Leases, Problems of Taxation, Finance, and Accounting," by Albert H. Cohen.